2017
DOI: 10.1210/jc.2017-00930
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leucine-Rich α-2-Glycoprotein 1 Predicts Rapid eGFR Decline and Albuminuria Progression in Type 2 Diabetes Mellitus

Abstract: Plasma LRG1 predicts both albuminuria and CKD progression beyond traditional risk factors. It may play a role in the pathologic pathway leading to progression of DKD in T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…[62][63][64][65] Our findings in the BioMe cohort, consisting of mixed races of Western patients with diabetes, indicate that plasma LRG1 is associated with renal outcome. Of note, during the preparation of this report, similar findings regarding plasma LRG1 were reported in a T2DM patient cohort in Singapore by Liu et al 66 Thus, the prognostic role of LRG1 in DKD progression has been confirmed in two separate patient cohorts, further strengthening our observations and confirming the human relevance of LRG1 in the pathogenesis of DKD. Future studies are required to confirm the clinical implications of LRG1 and other angiogenesis factors in DKD, and to assess the efficacy of urinary LRG1 detection as a prognostic marker of DKD progression.…”
Section: Discussionsupporting
confidence: 90%
“…[62][63][64][65] Our findings in the BioMe cohort, consisting of mixed races of Western patients with diabetes, indicate that plasma LRG1 is associated with renal outcome. Of note, during the preparation of this report, similar findings regarding plasma LRG1 were reported in a T2DM patient cohort in Singapore by Liu et al 66 Thus, the prognostic role of LRG1 in DKD progression has been confirmed in two separate patient cohorts, further strengthening our observations and confirming the human relevance of LRG1 in the pathogenesis of DKD. Future studies are required to confirm the clinical implications of LRG1 and other angiogenesis factors in DKD, and to assess the efficacy of urinary LRG1 detection as a prognostic marker of DKD progression.…”
Section: Discussionsupporting
confidence: 90%
“…LRG1 is upregulated in the glomerular endothelial cells isolated from streptozotocin-induced diabetic eNOS null mice as the model of diabetic nephropathy 32 . Moreover, LRG1 independently predicts the progression of albuminuria more strongly than traditional risk factors, including baseline eGFR and urine albumin to creatinine ratio 31 . In previous work, the level of plasma LRG1 was found to neither be affected by age nor by dialysis vintage on ESRD patients.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies showed that LRG1 promotes pathogenic neovascularization by binding to endoglin and subsequent activation of the TGF-β signaling pathway in endothelial cells 29,30 . In a 3-year prospective study of type 2 diabetes patients, a higher LRG1 level at baseline predicts higher risk for progression of albuminuria as well as eGFR decline independently 31 . LRG1 is upregulated in the glomerular endothelial cells isolated from streptozotocin-induced diabetic eNOS null mice as the model of diabetic nephropathy 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies from our group and others have shown that LRG is increased in various immune-related diseases such as adult-onset Still's disease 19 , psoriasis 20 , juvenile idiopathic arthritis 21 , Kawasaki disease 22 , appendicitis 23 and cancers 24,25 , indicating that LRG elevation is not limited to autoimmune diseases. In addition, LRG may serve as a biomarker for several other disease conditions such as heart failure 26 , diabetes-related complications [27][28][29] and obesity 30 , which are not typical inflammatory www.nature.com/scientificreports www.nature.com/scientificreports/ diseases but may involve immunopathogenic mechanisms. Thus, for diagnosis of active TB, LRG should be used in conjunction with other laboratory tests such as IGRA.…”
Section: Discussionmentioning
confidence: 99%